2009
DOI: 10.1002/ejic.200900598
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Structures and Photophysical Properties of Nine‐Coordinate Europium(III) Complexes with Tandem‐Connected Tridentate Phosphane Oxide Ligands

Abstract: Structures and photophysical properties of f-block metal complexes with tandem-connected tridentate phosphane oxide ligands, {bis [o-(diphenylphosphoryl) (DPPPO) and Eu(hfa) 3 (DPBTPO) provide characteristic distorted, capped square antiprism structures with nine-coordinate oxygen atoms. The emission properties related to the electric transition are characterized by the emission spectra, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 63 publications
1
32
2
Order By: Relevance
“…The radiative rate constant of Eu(tmh)3(tppo) (kr = 0.7×10 3 ) is slightly larger than that of Eu(hfa)3(tppo)2 (kr = 0.5×10 3 ) in solution. [25] The spectral shape of Eu(tmh)3(tppo) is also different from that of Eu(hfa)3(tppo)2 in solution. We consider that the geometrical structure of Eu(tmh)3(tppo) in solution might be pseudo-eightcoordinate structure.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The radiative rate constant of Eu(tmh)3(tppo) (kr = 0.7×10 3 ) is slightly larger than that of Eu(hfa)3(tppo)2 (kr = 0.5×10 3 ) in solution. [25] The spectral shape of Eu(tmh)3(tppo) is also different from that of Eu(hfa)3(tppo)2 in solution. We consider that the geometrical structure of Eu(tmh)3(tppo) in solution might be pseudo-eightcoordinate structure.…”
Section: Resultsmentioning
confidence: 97%
“…The Ln(tmh)3(tppo) exhibited small knr values, although the tBu groups in the complexes are composed of high-vibrational frequency C-H bonds (2950 cm -1 ). [25] High-vibrational C-H bonds generally promote effective thermal relaxation from the excited state of lanthanide complexes. [39] We have suggested that introducing low-vibrational frequency group such as C-F(1200 cm -1 ) instead of C-H was available for suppression of the thermal quenching like Eu(hfa)3(tppo)2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic ligands also enhance the radiative rate by introducing an asymmetric geometry around the lanthanide ion, effectively [9][10][11][12]. Based on their two strategies for design of the ligands, various types of strong luminescent lanthanide complexes with asymmetric structures have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prepare an intensely luminescent lanthanide complex, a large radiative rate constant based on reducing the geometrical symmetry and a small non-radiative rate constant by introducing low-vibrational frequency organic ligands should be required [16][17][18][19]. Previously, we have reported on two asymmetric Eu(III) complexes with low-vibrational frequency hexafluoroacetylacetonato (hfa) and bidentate phosphine oxide ligands, 4,5-bis(diphenylphosphoryl)-9,9-dimethylxanthene Eu(hfa) 2 (xantpo) 2 , and 4,5-bis(di-tert-butylphosphoryl)-9,9-dimethylxanthene Eu(hfa) 3 (tBu-xantpo) ( Fig.…”
Section: Introductionmentioning
confidence: 99%